Construction of specific erythromycin resistance mutations in the temperate lactococcal bacteriophage TP901-1 and their use in studies of phage biology. - Koch, B (1997)
A method for the construction and isolation of specifically designed mutations of the temperate lactococcal phage TP901-1 has been developed. Two different erm-labeled mutants were isolated. One was shown to be defective in lysogenization and excision. The other, showing normal lysogenization, was used for host range studies.